Level of interest and performance of tourism facilities in the attraction of the peak tourism of Paragliding - Fariansyah, Ilham; Pasaribu, Pasaribu (Universitas Negeri Padang, 2022)
This research started from observations, which were seen based on data from Puncak Paragliding tourist visits which decreased from January to September, this occurred due to the outbreak of the Covid - 19 pandemic that entered and resulted in the imposition of a lockdown system or PSBB in almost all regions in Indonesia including the city of Padang. . Where the government prohibits residents from making tourist visits in order to prevent the transmission of the Covid-19 pandemic. Only in the last three months of 2021 has the level of tourist visits coming to the Puncak Paragliding tourist attraction experienced a significant increase, this is of course accompanied by implementing strict health protocols. Researchers also observe other problems, namely as a tourist attraction Puncak Paragliding is faced with the challenge of being able to attract tourists who want to visit. This is certainly important to do because as one of the businesses engaged in services. In addition, facilities are facilities and infrastructure that play an important role in efforts to increase tourist satisfaction. The results showed that there were 6 indicators in quadrant 1 (Concentrate Here, Top Priority) High Importance, Low Performance, there were 2 indicators in quadrant 2 (Keep Up The Good Work, Maintain Performance) High Importance, High Performance, there were 2 indicators that are in quadrant 3 (Low Priority) Low Importance, Low Performance and there are 3 indicators that are in quadrant 4 (Possibly Overkill, Excessive) Low Importance, High Performance.